2004
DOI: 10.1136/jech.2003.015297
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for public health policy on inequalities: 2: Assembling the evidence jigsaw

Abstract: Study objective: To garner research leaders' perceptions and experiences of the types of evidence that influence policy on health inequalities, and their reflections on how the flow of such research evidence could be increased. Design, setting, and participants: Qualitative two day residential workshop with senior research leaders, most of whom were currently involved in evaluations of the health effects of major policies. In four in depth sessions, facilitated by the authors in turn, focused questions were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(144 citation statements)
references
References 9 publications
3
139
0
2
Order By: Relevance
“…They found that in addition to primary studies and systematic reviews, the types of evidence used included, internal program evaluations, local and provincial best practices, and natural policy experiments among others. In addition the categories tally with the five types of evidence influencing policy on health inequalities that Whitehead and colleagues (29) identified as particularly persuasive with policy-makers. These included observational evidence showing the existence of a problem; narrative accounts of the impacts of policies from the household perspective; controlled evaluations; natural policy experiments; and historical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…They found that in addition to primary studies and systematic reviews, the types of evidence used included, internal program evaluations, local and provincial best practices, and natural policy experiments among others. In addition the categories tally with the five types of evidence influencing policy on health inequalities that Whitehead and colleagues (29) identified as particularly persuasive with policy-makers. These included observational evidence showing the existence of a problem; narrative accounts of the impacts of policies from the household perspective; controlled evaluations; natural policy experiments; and historical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] In this case the various tenets from philosophy of science determine what is evidence and can be summarized as knowledge that is:…”
Section: Conceptualizing and Combining Evidence For Health System Guimentioning
confidence: 99%
“…8 The research community's view of evidence, although not uniform, is narrower and generally restricted to information generated through a prescribed set of processes and procedures recognized as scientific. [10][11][12][13][14] In this case the various tenets from philosophy of science determine what is evidence and can be summarized as knowledge that is:…”
Section: Section 1: What Counts As Evidence? Two Views Of Evidence -Cmentioning
confidence: 99%
“…Absolute inequality may change without change in relative inequalities (Ravallion, 2003). A generalized theory of inequality transitions or life cycle of inequality transition has applied to a broad range of domains: change in the shape and composition of between-nations or global inequality, within national inequalities and social inequalities (Whitehead et al, 2004).…”
Section: Health Inequalitiesmentioning
confidence: 99%